Development of robotic arm plotter for disable people - Bhuiyan, Moinul; Muhammad , Muaz (2014)

(untitled)
Robotic arm plotter was widely used as a drawing tool in the world of art. The robot used two degree of freedom in order to achieve the movement to the specific angle and coordinates. The forward kinematics of the robot has been solved by Denavit-Hartenberg representation while the inverse kinematics was solved by analytic method. User interface application was created via Arduino software and the data was sent to the microcontroller. Later, the microcontroller will send out the instruction to the actuator and the robot moves to the desired position, sketching the word ‘IIUM’.